Manajemen Tata Ruang dalam Meningkatkan Kinerja Pegawai di Kantor Bidang Pendidikan Madrasah Kanwil Kemenag Jatim - Nada, Nadiyah Qothrotun; Rohmah, Atiyah Manzilatur; Al Bahjah, Zahin Rafsanjani; Huriyah, Lilik; Rahmadani, Surya (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2023)
Management is an important and necessary thing in human life. Skilled people can properly manage the organization according to the existing management arrangements. Organizations consist of a group of people who are organized and work together to achieve goals. Office layout management in public organizations plays an urgent role as a supporting element for management in achieving organizational goals. In this sense, agencies must improve their operational systems by increasing the quality of public services to create satisfaction. This research is a qualitative research. The main objective of this research is to determine the implementation of spatial management in an effort to improve employee performance in the Madrasah Education Office of the East Java Regional Office of the Ministry of Religion. Better office layout will influence employee satisfaction and increase productivity. The background is due to the arrangement of office spaces and the arrangement of office spaces which are connected by seating dividers for each individual and grouped according to the role of each individual. Office layout is the arrangement of office space, office equipment and office furniture in the correct location to support the achievement of office goals efficiently and effectively.